Psychometric properties and validation of the revised Chinese Medication Literacy Scale for Hypertensive Patients (C-MLSHP-R) - Qin, Ning; Duan, Yinglong; Yao, Ziqiang; Shi, Shuangjiao; Liu, Haoqi; Li, Xiao; Zheng, Feng; Zhong, Zhuqing (Frontiers in Cardiovascular Medicine, 2022)
Background: Medication literacy was one of the key indicators that can affect the self-management of medications and medication safety. This study aimed to revise the medication literacy scale for hypertensive patients (C-MLSHP) and test the reality and validity of the revised scale. Methods: We revised the C-MLSHP by several methods, i.e., focus group discussion, expert consultation, patient interview, and pilot study, based on the established evaluation index system of medication literacy for hypertensive patients. Then, a formal survey using the revised Chinese medication literacy scale for hypertensive patients (C-MLSHP-R) was carried out on hypertensive patients from hospitals and community healthcare centers in Changsha city of China to test its reality and validity. The reliability was evaluated with Cronbach’s α coefficient, split-half reliability, and test-retest reliability. The validity was evaluated with content validity, construct validity, convergent validity, discriminant validity and criterion-related validity. Results: The C-MLSHP-R contained 18 items within four domains, i.e., knowledge domain included 4 items, attitude domain had 3 items, skill domain involved 7 items, and practice domain included 4 items. A total of 339 hypertensive patients participated in the formal survey. The results showed that the Cronbach’s α coefficient of C-MLSHP-R was 0.802, and for each domain ranged from 0.639 to 0.815. The split-half reliability coefficient of C-MLSHP-R was 0.709, and for each domain ranged from 0.648 to 0.792. The test-retest reliability coefficient of C-MLSHP-R was 0.851, and for each domain ranged from 0.655 to 0.857. The I-CVI of each item ranged from 0.833 to 1.000, the S-CVI/Ave of C-MLSHP-R was 0.981, the S-CVI/UA was 0.889 and for each domain ranged from 0.958 to 1.000. Confirmatory factor analysis results showed that the model fitted well. The convergent validity of C-MLSHP-R was acceptable, and the discriminant validity was good. The criterion coefficient between C-MLSHP-R and C-MLSHP was 0.797, and for each domain ranged from 0.609 to 0.755. Conclusion: Compared with C-MLSHP, the C-MLSHP-R with 18 items was much shorter for measuring, had decreased reliability within the acceptable range and better validity, which was more appropriate and time-saving to assess the medication literacy level for hypertensive patients scientifically and conveniently.